Joint Dysfunctionality Alleviation along with Systemic Inflammation Reduction Following Arthrocen Treatment in Patients with Knee Osteoarthritis: A Randomized Double-Blind Placebo-Controlled Clinical Trial - Ramin Goudarzi; Peter Thomas; Sandra Ryan (Medicina, 2022)
Background and objectives: Many mediators and cytokines are involved in the pathogenesis of osteoarthritis (OA). Some of these cytokines are spontaneously expressed by cultured fibroblast-like synoviocytes. Therefore, using serum samples, the efficacy and the effects of avocado/soy unsaponifiables, ASU, (Arthrocen) on cytokine changes were assessed in patients with knee OA (KOA). Materials and Methods: Experimental procedure: A randomized, double-blind, placebo-controlled clinical trial was conducted on patients with a diagnosis of mild to moderate OA who received either Arthrocen 300 mg/day (n = 61) or placebo (n = 58) for 3 months. Data collection was performed using questionnaires including the Western Ontario and McMaster Universities osteoarthritis index (WOMAC), 20-item short form survey (SF-20), Lequesne index of severity for osteoarthritis of the knee (LISOK), and three visual analog scales (VASs) as pain quality indices. The serum levels of interleukins 2 (IL-2), IL-4, IL-10, IL-17α, and TNF-α were measured using an ELISA reader. Results: Both quality of life indices, pain sensation and scored by specialists (as VASs), respectively, including WOMAC and SF-20, as well as joint dysfunctionality symptoms assessed by physicians were significantly improved (p < 0.05) in OA patients receiving Arthrocen. The serum levels of anti-inflammatory interleukins 4 and 10 were also augmented, while levels of inflammatory IL-17 and TNF-ɑ cytokines were decreased significantly (p < 0.05) compared with the control groups during the 3- and 6-month treatment. Conclusions: Arthrocen consumption may increase the quality of life in OA patients through amelioration of inflammation and improvement of functional activities without any adverse effects in the long term.